2013
DOI: 10.1186/scrt318
|View full text |Cite
|
Sign up to set email alerts
|

Mechanically induced osteogenic lineage commitment of stem cells

Abstract: Bones adapt to accommodate the physical forces they experience through changes in architecture and mass. Stem cells differentiate into bone-forming osteoblasts, and mechanical stimulation is involved in this process. Various studies have applied controlled mechanical stimulation to stem cells and investigated the effects on osteogenic lineage commitment. These studies demonstrate that physical stimuli can induce osteogenic lineage commitment. Tension, fluid shear stress, substrate material properties, and cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
116
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(118 citation statements)
references
References 81 publications
2
116
0
Order By: Relevance
“…Mechanical stress-induced alterations in cell shape and structure are vital for the control of cell growth, migration, differentiation, and apoptosis (Chicurel et al 1998). Mechanical forces and matrix mechanical properties impact the cytoskeletal tension and regulate stem cell lineage commitment in part by Rho/ROCK signaling (Chen and Jacobs 2013;Ivanovska et al 2015). Recent studies shed light on the striking roles of transcriptional regulators Yes-associated protein (YAP)/transcriptional coactivator with PDZ-binding motif (TAZ), which are the downstream effectors of the Hippo pathway (Pan 2010), in mechanotransduction.…”
Section: Mechanotransductionmentioning
confidence: 99%
“…Mechanical stress-induced alterations in cell shape and structure are vital for the control of cell growth, migration, differentiation, and apoptosis (Chicurel et al 1998). Mechanical forces and matrix mechanical properties impact the cytoskeletal tension and regulate stem cell lineage commitment in part by Rho/ROCK signaling (Chen and Jacobs 2013;Ivanovska et al 2015). Recent studies shed light on the striking roles of transcriptional regulators Yes-associated protein (YAP)/transcriptional coactivator with PDZ-binding motif (TAZ), which are the downstream effectors of the Hippo pathway (Pan 2010), in mechanotransduction.…”
Section: Mechanotransductionmentioning
confidence: 99%
“…1 This process is called mechanotransduction, and the responsible structures sensitive to mechanical forces are most probably cytoskeleton elements. 2 A number of studies have demonstrated that cells are sensitive to several kinds of physical cues (shear stress, topography, mechanical deformation, etc), influencing cell migration, 3 differentiation, 4 and proliferation. 5 Among these stimuli, gravity is required for the correct development of land-based organisms, and in particular for the skeleton and for the muscle and nervous systems.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, some ECMs are known to modulate cell functions and have been termed as 'matricellular' proteins (3). During the process of osteogenesis in vivo, MSCs proliferate and then differentiate into osteoblastic cell lineage in a microenvironment associated with a heterogeneous population of cells and ECMs, under the influence of cell-cell and cell-matrix interactions (8). Therefore, for better understanding of the mechanism of mechanical stress-stimulated osteoblastogenesis, a global analysis needs to be performed to examine the cellular response to mechanical stress in a microenvironment similar to that found in vivo.…”
Section: Methodsmentioning
confidence: 99%
“…Mechanical stress controls bone mass by affecting recruitment of osteoprogenitors as well as osteoblast differentiation from mesenchymal stem cells (MSCs) in the bone tissue (7,8). Elucidation of the precise mechanisms involved in the osteoblastogenesis stimulated by mechanical stress, especially the mechanism for osteogenic differentiation of MSCs, will contribute to the progress of regenerative medicine for effective production of bone tissue from MSC sources.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation